141k views
5 votes
PLEASE HELP! I'M ON A TIMER

A rope is swinging in such a way that the length of the arc traced by a knot at its bottom end is decreasing geometrically. If the third arc is 18 ft. long and the seventh arc is 8 ft. long, what is the length of the arc on the sixth swing? Round your answer to the nearest tenth of a foot.

User Angrykoala
by
6.0k points

2 Answers

3 votes

Answer:

Length of the arc on the sixth swing = 9.80 ft

Step-by-step explanation:

A rope is swinging in such a way that the length of the arc traced by a knot at its bottom end is decreasing geometrically.

Length of 3rd arc = 18 ft

Length of 7th arc = 8 ft

We have to find the length of arc formed in a the 6th swing.

As we know in a geometric sequence, explicit formula is given as


a_(n)=a(r)^(n-1)

where
a_(n) is the nth term, a is the first term, r is the common ratio and n is the number of term

Now for 3rd term of the sequence ⇒
a_(3)=a(r)^(2)=18------(1)

For 7th term of the sequence ⇒
a_(7)=a(r)^(7-1)=ar^(6)=8 ------(2)

Now we divide equation 2 from equation 2


(a_(7))/(a_(3) )=(a.r^(6))/(a.r^(2))=(8)/(18)

we solve it further


r^(4)=(4)/(9)


r^(2)=\sqrt{(4)/(9)}=(2)/(3)


r=\sqrt{(2)/(3)}=√(0.667)=0.817

Now we put the value of r in equation 1

a.r² = 18

a.(√0.667)²= 18

a×0.667 = 18 ⇒ a = 26.986

Now we will calculate the 6th term of this sequence


a_(6)=(26.99).(0.0.817)^(6-1)=(26.99)(0.817)^(5)=(26.99).(0.363)=9.80

Answer is Length of the arc on the 6th swing = 9.80 ft

User Vmvadivel
by
5.9k points
1 vote
The correct answer is 9.8 ft.

Step-by-step explanation:
This is a geometric sequence, which follows the explicit formula

g_n=g_1* r^(n-1)

where g
is the first term, r is the common ratio and n is the term number.

We know that the third term is 18; this gives us 18=g
₁×r³⁻¹ or 18=g₁×r².

We also know the seventh term is 8, which gives us 8=g
₁×r⁷⁻¹ or 8=g₁×r.

Solving for g
in the third term gives us g=18/r², and solving for g in the seventh term gives us g=8/r. They both equal g so we set them equal to each other:

18/r
² = 8/r.
Multiply both sides by r
, which gives us
18r
/r² = 8.

Using our properties of exponents, we have 18r
= 8. Divide both sides by 18, which gives us
r
=8/18.

We can find the fourth root by taking the square root twice:
taking the square root gives us r
² = 8/18.

Simplifying
8 we get 22, and simplifying 18 gives us 32; we now have

r
²=22)/32.

The
2 will cancel, leaving r²=2/3. Taking the square root again, we have

r=
2/3; simplifying this gives us r=6/3.

We can now work backward to find the sixth term using the seventh one; Divide 8 by
6/3. Dividing by a fraction means multiplying by the reciprocal, so we multiply 8 by 3/6; this gives us 24/6, and in a calculator that gives us 9.8 ft.
User Mark Allison
by
5.2k points